Numerical Analysis of Hip Joint Implant. (2015) - Saxena, Arjit Kumar; Misra, Raghvendra Kumar; Dixit, Anurag
Abstract: Bones form the rigid skeletal framework of the body which deftly protect the internal vital organs along with allowing various movements and tasks at the different kinds of joints formed by these bones. It is a well – known fact that there are 206 bones in the adult body. However, this skeleton over which our entire body is structured is highly prone to get affected by trauma. Any trauma to any bone in the body can be mighty painful for the patient. These situations are dealt with by Orthopaedic surgeons. When trauma is suffered by Femur, the longest and strongest bone of the body, forming the length of the thigh, it becomes an emergency as often the patient is an elderly with weak bones and, if not attended to on time, this fracture can lead to massive blood loss. In elderly patients, a mere repair of the fracture of femur doesn't work. It is required to make their bone strong enough to bear the weight of the body again. For this, surgeons often use implants made of biomaterials like Titanium. A comparative study has been performed between Titanium, Stainless Steel and Aluminium made implant.